First record of the tropical-subtropical genus Ugandatrichia Mosely (Trichoptera, Hydroptilidae) from a temperate zone, with description of a new species - Ito, Tomiko; Nishimoto, Hiroyuki; Nishimoto, Futaba (Zootaxa, 2018)
The tropical-subtropical caddisfly genus Ugandatrichia Mosely (Hydroptilidae) is recorded for the temperate zone and the Palearctic region for the first time, with description of a new species, U. shinshiroensis from central Japan. The adults and immature stages are described with notes on their ecology.